2021
DOI: 10.2110/jsr.2020.013
|View full text |Cite
|
Sign up to set email alerts
|

Deformation–sedimentation feedback and the development of anomalously thick aggradational turbidite lobes: Outcrop and subsurface examples from the Hikurangi Margin, New Zealand

Abstract: Concepts of the interaction between autogenic (e.g., flow process) and allogenic (e.g., tectonics) controls on sedimentation have advanced to a state that allows the controlling forces to be distinguished. Here we examine outcropping and subsurface Neogene deep-marine clastic systems that traversed the Hikurangi subduction margin via thrust-bounded trench-slope basins, providing an opportunity to examine the interplay of structural deformation and deep-marine sedimentation. Sedimentary logging and mapping of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 127 publications
1
26
0
Order By: Relevance
“…Data are extracted from Pirmez et al (2000), Bruhn et al (2003), Moraes et al (2004), Prélat et al (2009, 2010, and is locally accumulated. Such bypass and overspill processes are typical of intraslope sub-basins as also described from other geological contexts (Sinclair and Tomasso, 2002;Prather, 2003;McArthur et al, 2021). Studied lobe fringes record few bipartite beds, which are diagnostic for basin floor lobe fringe deposits (Hodgson, 2009).…”
Section: Net-to-gross Facies and Processessupporting
confidence: 61%
See 1 more Smart Citation
“…Data are extracted from Pirmez et al (2000), Bruhn et al (2003), Moraes et al (2004), Prélat et al (2009, 2010, and is locally accumulated. Such bypass and overspill processes are typical of intraslope sub-basins as also described from other geological contexts (Sinclair and Tomasso, 2002;Prather, 2003;McArthur et al, 2021). Studied lobe fringes record few bipartite beds, which are diagnostic for basin floor lobe fringe deposits (Hodgson, 2009).…”
Section: Net-to-gross Facies and Processessupporting
confidence: 61%
“…These perched lobes are also described as confined lobes, of which an important literature is available from outcrop, with for example the world class Annot Sandstones, France (Joseph et al, 2000;Guillocheau et al, 2004;Joseph and Lomas, 2004;Etienne et al, 2012), the Sorbas basin, Spain (Kleverlaan, 1989;Postma and Kleverlaan, 2018) or the Hikurangi margin, New Zealand (Burgreen and Graham, 2014;McArthur et al, 2021), and from modern system such as the Golo system, East Corsica (Gervais et al, 2004(Gervais et al, , 2006Deptuck et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Deceleration may lead to the formation of more chaotic, yet still weakly‐confined, flow deposits. Anomalously high‐amplitude reflectors observed above sheet deposits with variable amplitudes may reflect sand‐rich deposits from weakly‐confined flows (McArthur et al ., 2021) after initial MTD‐margin topography was healed, leaving a less severe reduction in longitudinal gradient. These deposits formed immediately prior to, and during, re‐incision and may mark the transition from incised sheet to terrace deposits.…”
Section: Resultsmentioning
confidence: 99%
“…The trench fill decreases in thickness from ca 6 km in the south‐west to ca 1 km in the north‐east (Lewis et al ., 1998; Barnes et al ., 2010; Plaza‐Faverola et al ., 2012). The fill dominantly comprises turbidites resulting from overbank deposition from the Hikurangi Channel, and transverse drainage networks that traversed the bounding slope (Lewis, 1994; Lewis et al ., 1998; Mountjoy et al ., 2009; McArthur et al ., 2021).…”
Section: Geological Settingmentioning
confidence: 99%
“…Nonetheless outcrop examples where tectonic control of sea floor gradients can be demonstrated are rare. Amongst those described are tectonically-forced lateral migration of channels and fans in the Ainsa Basin, northern Spain (Pickering and Corregidor, 2005;Tek et al, 2020), flow stripping across an emergent fault-scarp in the Annot Basin (Tomasso and Sinclair 2004), sandy lobes aggrading behind thrust-related folds in a trench slope setting on the Hikurangi Margin (McArthur et al, 2021), changes in bed type related to tectonic evolution of the Apennines foredeep (Tinterri and Muzzi Magalhaes, 2011;Tinterri and Piazza, 2019) and evidence for faulting on the floor of late Miocene basins in SE Spain (Haughton, 2000;Hodgson and Haughton, 2004). The study reported here builds on the first recognition of an important intrabasinal fault zone traversing the floor of the southern Tabernas Basin, SE Spain (Haughton, 2000).…”
Section: Introductionmentioning
confidence: 99%